Editorial - David Cabello Manrique (Universidad de Granada, 2019)
Racket Sports have been widely studied in science for the last years. The purpose of this Journal is to aggregate the most important advances and researches to affect the development and directions of racket sports science from now on. To reflect on the importance and impact a specialized journal can have in the field, we can put some perspective on its development: • In 1993, the series of World Congresses in Science and Racket Sports took place, causing several publications to be released subsequently. • Sharp (1998), recorded the duration of the rallies and the work-rest ratio in squash, using technology. • The following years, the increase in computing power allowed to carry on studies with an unthinkable amount of data.